The unmothers : a novel - Anderson, Leslie (Leslie J.) (Quirk Books, 2024)
"Marshall, a journalist, is sent to a small town to look into an improbable rumor that a horse has given birth to a human baby. As she investigates, she discovers evidence of a murder and becomes drawn into an even deeper and stranger mystery than she expected"--